Philosophical Foundations in the Development of the Arabic Language Curriculum - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This study discusses the philosophical foundations in the development of the Arabic language curriculum as a conceptual basis that determines the direction, content, and teaching methods. The Arabic curriculum is not only designed to teach linguistic skills but also to cultivate a deep understanding of human, intellectual, and spiritual values within the framework of educational philosophy. The aim of this study is to identify and analyze the philosophical aspects underlying the development of the Arabic curriculum, particularly from the perspectives of ontology, epistemology, and axiology. This research employs a qualitative approach using a literature review method, examining various primary and secondary sources such as books, journals, and relevant curriculum documents. Data collection was carried out through documentation and analyzed using descriptive-analytical techniques. The results show that the Arabic language curriculum should be built upon a comprehensive philosophical understanding: ontologically affirming the existence of language as a medium of revelation and culture; epistemologically supporting the construction of knowledge through both scientific and religious approaches; and axiologically emphasizing the importance of moral, ethical, and meaningful values in the learning process. These findings underscore the urgency of integrating philosophical dimensions in the development of the Arabic language curriculum to make it more holistic, relevant, and transformative.